Local bias induced ferroelectricity in manganites with competing charge and orbital order states - Figueiras, Fabio G. N.
Perovskite-type manganites, such as Pr1-xCaxMnO3, La1-xCaxMnO3 and La1-xSrxMnO3 solid solutions, are set forth as a case study of ferroelectricity formation mechanisms associated with the appearance of site- and bond- centered orbital ordering which breaks structural inversion symmetry. Even though the observation of macroscopic ferroelectricity may be hindered by the finite conductivity of manganites, polarization can still exist in nanoscale volumes. We use Piezoresponse Force Microscopy to probe local bias induced modifications of electrical and electromechanical properties at the manganite surface. Clear bias-induced piezocontrast and local hysteresis loops are observed for La0.89Sr0.11MnO3 and Pr0.60Ca0.40MnO3 compounds providing convincing evidence of the existence of locally induced polar states well above the transition temperature of the CO phase, while the reference samples without CO behavior show no ferroelectric-like response. Such coexistence of ferroelectricity and magnetism in manganites due to the charge ordering (CO) under locally applied electric field opens up a new pathway to expand the phase diagrams of such systems and to achieve spatially localized multiferroic effects with a potential to be used in a new generation of memory cells and data processing circuits.